A pathway‐based association analysis identified FMNL1‐MAP3K14 as susceptibility genes for leprosy. Issue 3 (8th February 2018) - Zhang, Huimin; Wang, Zhenzhen; Fu, Xi'an; Sun, Yonghu; Mi, Zihao; Yu, Gongqi; Sun, Lele; Wang, Na; Wang, Chuan; Zhao, Qing; Pan, Qing; Yue, Zhenhua; et al.
Abstract: The nuclear transcription factor‐κB (NF‐κB) plays a pivotal role in controlling both innate and adaptive immunity and regulates the expressions of many immunological mediators. Abundant evidences have showed the importance of NF‐κB pathway in the host immune responses against Mycobacterium leprae in the development of leprosy. However, no particular association study between leprosy and NF‐κB pathway‐related gene polymorphisms was reported. Here, we performed a large‐scale and two‐stage candidate association study to investigate the association between 94 NF‐κB pathway‐related genes and leprosy. Our results showed that rs58744688 was significantly associated with leprosy ( P  = 7.57 × 10 −7, OR = 1.12) by combining the previous genomewide association data sets and four independent validation sample series, consisting of a total of 4631 leprosy cases and 6413 healthy controls. This founding implicated that MAP3K14 and FMNL1 were susceptibility genes for leprosy, which suggested the involvement of macrophage targeting and NF‐κB pathway in the development of leprosy.